2022
DOI: 10.3390/life12060866
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised High-Performance Oxide Ceramics with Bone Morphogenic Protein 2 (BMP-2) Induced Ossification: An In Vivo Study

Abstract: This study investigated the in vivo osseointegration potential of high-performance oxide ceramics (HPOCs) with peptide bone morphogenic protein 2 (BMP-2), comparing them with titanium implants. Histomorphometry was conducted around the distal, proximal, medial, and lateral sides of the implants to quantify the amount of mature and immature ossification within the bone interface. We hypothesised that HPOCs functionalised with BMP-2 promote ossification. HPOCs functionalised with BMP-2 were manufactured at the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Increase in BV/TV, Conn.D, Tb.Th and Tb.N. in Group I than other groups Migliorini et al [ 49 ] 36 female New Zealand white rabbits Lateral femoral condyles BMP-2 coated HPOC (group I) versus sandblasted titanium implants (group II) 6, 12 weeks The bone implant contact of BMP-2 coated HPOC increased similarly to standard titanium implants Migliorini et al [ 50 ] 36 female New Zealand white rabbits Lateral femoral condyles RGD coated HPOC (group I) versus sandblasted titanium implants (group II) 6, 12 weeks The bone implant contact of RGD coated HPOC increased similarly to standard titanium implants Plaza et al [ 54 ] 42 New Zealand white rabbits Medial femoral condyles Physical incorporation of fibronectin in HA bulk material by adding HA to a fibronectin solution of in PBS 1,2,5 days Increase in Tb.Th in Group I in the area next the screw in comparison with area far from the device Increase in cellularity at 24 h in Group I than the other Groups Shen et al [ 55 ] 43 New Zealand white rabbits Femoral epiphysis TNT were immersed in supersaturated Ca(OH) 2 solution, Ca(NO 3 ) 2 ·4H 2 O (0.2 M) and (NH4)2HPO4 (0.2 M) solutions to create a coating of HA. TNT-HA was subsequently functionalized with Aln by immersion in Aln solution (physical absorption) 12 weeks no dislocation and inflammation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in BV/TV, Conn.D, Tb.Th and Tb.N. in Group I than other groups Migliorini et al [ 49 ] 36 female New Zealand white rabbits Lateral femoral condyles BMP-2 coated HPOC (group I) versus sandblasted titanium implants (group II) 6, 12 weeks The bone implant contact of BMP-2 coated HPOC increased similarly to standard titanium implants Migliorini et al [ 50 ] 36 female New Zealand white rabbits Lateral femoral condyles RGD coated HPOC (group I) versus sandblasted titanium implants (group II) 6, 12 weeks The bone implant contact of RGD coated HPOC increased similarly to standard titanium implants Plaza et al [ 54 ] 42 New Zealand white rabbits Medial femoral condyles Physical incorporation of fibronectin in HA bulk material by adding HA to a fibronectin solution of in PBS 1,2,5 days Increase in Tb.Th in Group I in the area next the screw in comparison with area far from the device Increase in cellularity at 24 h in Group I than the other Groups Shen et al [ 55 ] 43 New Zealand white rabbits Femoral epiphysis TNT were immersed in supersaturated Ca(OH) 2 solution, Ca(NO 3 ) 2 ·4H 2 O (0.2 M) and (NH4)2HPO4 (0.2 M) solutions to create a coating of HA. TNT-HA was subsequently functionalized with Aln by immersion in Aln solution (physical absorption) 12 weeks no dislocation and inflammation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…These surfaces already provide substantial primary stability in cancellous bone 46 thus limiting micromotion before osteointegration. [47][48][49][50] Their surfaces also strongly promote osseointegration through the bone on-or ingrowth. 51 One reason why the topic of cementless implant fixation in TKA is also more and more relevant is the fact, that a cemented interface never osseointegrates and thus also does not allow bone-remodelling according to functional requirements placed on it.…”
Section: Fixationmentioning
confidence: 99%
“…70 For TKA, two main approaches have been chosen: the manufacturing of full-thickness ceramic implants and the creation of ceramic surfaces. [48][49][50] To date, the company PETER BREHM GmbH (Weisendorf, Germany) is the only manufacturer worldwide that offers an all-ceramic primary knee endoprosthesis (BPK-S INTEGRATION Ceramic). Smith & Nephew (London, England) additionally provides a prosthesis (LEGION) where, even if not the tibial component, at least the femoral component is made of solid ceramic consisting of Zirconium and Niob.…”
Section: Bearingmentioning
confidence: 99%
“…BMP-2 also activates the NFATc1 transcription factor, a key transcription factor for osteoclast differentiation [ 118 ]. As well as stimulating bone mineralization, BMP-2 has been shown to stimulate the differentiation of MSCs into mature osteoblasts [ 119 ]. Logically, Smad1 is phosphorylated and activated by BMP-2 binding to the BMP receptor, leading to Runx2 translocation to the nucleus of pre-osteoblast cells to upregulate osteogenic factors, including ALP and OCN [ 120 ].…”
Section: Regulation Of Bone Homeostasis By the Macrophage–osteoclast ...mentioning
confidence: 99%
“…Interleukins associated with the inhibition of osteogenesis were not detected in exosomes released from LPS-stimulated macrophages in a culture medium. It has also been demonstrated that exosomes produced by LPS-activated macrophages improve the secretion of Runx2 and BMP-2 in BMSCs and promote osteogenic differentiation [ 119 ]. This suggests that exosomes released from macrophages may have a role in regulating bone homeostasis that is not identical to that of macrophages.…”
Section: Regulation Of Bone Homeostasis By the Macrophage–mesenchymal...mentioning
confidence: 99%